DESIGNING SPBU (SPEAKING BUSINESS) BASED ON ANDROID APPLICATION FOR SHARIA ECONOMIC STUDENTS - Hanifah, Denoena (Universitas Mahaputra Muhammad Yamin, 2023)
The aim of this research was to develop a learning media based on an Android application, which is believed to enable students to learn independently and enhance their communication skills for Sharia Economic students. The researcher employed the Research and Development (R&D) methodology to create the product. To complete the development of this product, the researcher adopted steps introduced by Maribe Branch known as the ADDIE model, which includes analysis, design, development, implementation, and evaluation.The target population for this research comprised third-semester students majoring in Sharia Economics at Universitas KH. A. Wahab Hasbullah Jombang, with a total of 12 students. Data collection for this research involved interviews and questionnaires. The results showed that the media expert data indicated 89%, demonstrating that the application was suitable to be used as an interesting and interactive English learning tool. The data from the material expert indicated 96%, confirming that the application was suitable for use in the learning process. During the implementation process, a score of 75% was achieved, indicating that the application helped students become more active and interested in class, enabling them to speak English more fluently during their learning process. In the final evaluation, it was found that this media was proven to be suitable for improving students' speaking skills in the specific subject of English for Sharia Economics.